Mid-century modernism and the American body : race, gender, and the politics of power in design - Wilson, Kristina (Princeton University Press, 2021)
"The first investigation of the role of how modernist objects were marketed by affirming buyers' racial and gender identities"-- Provided by publisher.
Keywords: Design -- Social aspects -- United States -- History -- 20th century.; Modernism (Aesthetics) -- Social aspects -- United States.; Decorative arts -- United States -- Marketing.; Power (Social sciences) -- United States -- History -- 20th century.; Industrial design -- Social aspects -- United States -- History -- 20th century.; Design -- Aspect social -- États-Unis -- Histoire -- 20e siècle.; Modernisme (Esthétique) -- Aspect social -- États-Unis.; ART / History / General.; Decorative arts -- Marketing; Design -- Social aspects; Power (Social sciences); United States; Modernismus; Produktgestaltung.; Industriedesign; Rassendiskriminierung; Gender; Ethnische Gruppe; USA; 1900-1999; Geschichte 1950-1960; Adam Green.; African American visual culture.; American design.; Barbara Miller Lane.; Beatriz Colomina.; Black advertising.; Brenna Wynn Greer.; Cold War on the Home Front.; Colonial Revival.; Dianne Harris.; Domesticity at War.; Donald Albrecht.; Greg Castillo.; Herman Miller.; Houses for a New World.; Ilana Harris-Babou.; Jochen Eisenbrand.; Little White Houses.; Lucinda Havenhand.; Pat Kirkham.; Paul R. Williams.; Russel Wright.; Selling the Race.; Tyler the Creator.; Wendy Kaplan.; Whiteness studies.; ashtrays.; consumer taste.; exotic accessories.; interior decorating.; suburbia.; History